Eddie [videorecording (DVD)] - Martin, Dylan Grey; Miller, Joseph; Rebeooack, Ross; Timphony, James (Random Media, 2024)
In the desert of Arizona, a gas station owner, enchanted by romance films, falls for a customer. He descends into fantasy, compelled to murder in desperate pursuit of a cinematic love story, blurring the lines between obsession and love.